Perancangan stasiun kerja instruktur laboratorium desain produk dan inovasi menggunakan metode ergonomic function deployment - Jessica Tesalonika; Benedikta Anna Haulian Siboro; Chrisdio Ebenezer Marbun (Universitas Mercu Buana, 2021)
The Product Design and Innovation Laboratory (Desprin), Faculty of Technology, Institute of Technology is a necessary facility in an effort to support the implementation of an educational process that implements a competency-based curriculum. This study aims to produce an ergonomic instructor workstation design in the laboratory by applying the Ergonomic Function Deployment (EFD), 12 ergonomic principles, and anthropometric data with the 5-95th percentile with selecting concepts from several concepts that have been designed. The final result of this research is a workstation design in the form of a drawing table, computer desk, and instructor chair designed using Solidworks 2018 software. The drawing table can be folded when not in use and attached to a computer table so that user movement is more effective and the selected chair is able to work synergistically with the two tables.